Grandparents' entitlements and obligations - Draper, Heather (Bioethics, 2013)
In this article, it is argued that grandparents' obligations originate from parental obligations (i.e from the relationship they have with their children, the parents of their grandchildren) and not from the role of grandparent per se, and any entitlements flow from the extent to which these obligations are met. The position defended is, therefore, that grandparents qua grandparents are not entitled to form or continue relationships with their grandchildren. A continuation of grandparent-grandchildren relationships may be in the interests of children, but the grandparental nature of the relationship is not decisive. What counts is the extent to which relationships children have with any adults who are not their parents are is significant to them. Sometimes, however, grandparents become parents or co-parents of their grandchildren. They then gain parental rights, and as such are as entitled, ceteris parius, as any parent to expect their relationship with the child to continue. The issue of grandparents' entitlements can come to the fore when parents separate, and grandparents are unhappy with the access they have to their grandchildren. Grandparents' obligations may become a particular issue when parents die, struggle, or fail to care for their children. This article focuses particularly on these kinds of circumstances.